2003
DOI: 10.1111/j.1348-0421.2003.tb03391.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ovine MHC Class IIDRB1Alleles on Immune Response in Bovine Leukemia Virus Infection

Abstract: We have reported previously that the alleles of the ovine leukocyte antigen (OLA)‐DRB1 gene that encode the Arg‐Lys (RK) motif and the Ser‐Arg (SR) motif at positions β70/71 of the OLA‐DRβ1 domain are associated with resistance and susceptibility, respectively, to development of bovine leukemia virus (BLV)‐induced ovine lymphoma. Here, to investigate the different immune response in sheep that carried alleles associated with resistance and susceptible for 30 weeks after infection with BLV, we selected sheep th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 38 publications
2
30
0
1
Order By: Relevance
“…DRB3 ( BoLA-DRB3 ) has been found to be highly polymorphic and is responsible for the differences in the susceptibility to infectious disease. DRB1 is a pseudogene and DRB2 gene is transcribed at very low levels in lymphocyte tissue [9, 10]. Polymorphism of BoLA-DRB3 is confined mainly to second exon that encodes for β 1 domain, responsible for peptide-binding sites.…”
Section: Introductionmentioning
confidence: 99%
“…DRB3 ( BoLA-DRB3 ) has been found to be highly polymorphic and is responsible for the differences in the susceptibility to infectious disease. DRB1 is a pseudogene and DRB2 gene is transcribed at very low levels in lymphocyte tissue [9, 10]. Polymorphism of BoLA-DRB3 is confined mainly to second exon that encodes for β 1 domain, responsible for peptide-binding sites.…”
Section: Introductionmentioning
confidence: 99%
“…In genetic analysis of BLV-infection, previous studies revealed the polymorphism in bovine leukocyte antigen (BoLA)-DRβ chain associated with resistance to expansion of BLV [27] and PL [28]. Furthermore, it appeared that ovine leukocyte antigen (Ovar)-DRB1 alleles encoding the RK motif at positions 70-71 of the Ovar-DRβ chain might protect against tumor development after experimental infection of sheep with BLV [29], and sheep with alleles encoding the RK motif could induce cellular immunity [30]. In this report, we showed that polymorphisms in the TNF-α promoter, -824G, which indicated low transcriptional activity, is associated with the BLV-induced lymphoma and elevation of provirus load in BLV-infected individuals.…”
mentioning
confidence: 99%
“…Such associations could be due to differences in disease resistance between carriers of various MHC haplotypes that can in turn affect the individual growth performance. In sheep, associations of DRB1 alleles with resistance to bovine leukaemia virus infection [16] or parasitic nematodes [26] are known. We found the birth weight of lambs to be significantly associated with DRB1 microsatellite alleles (Tab.…”
Section: Mhc Variants and Growth Traitsmentioning
confidence: 99%